Enhancing The Quality of Teaching Models in Developing The Characteristics of Early Childhood Education Through Project-Based Learning - Rahayu, Sri Rahayu; Priyanthi, Neeta (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2024)
In education, issues relating to learning models have always been a fascinating topic of conversation. This research aims to develop a teaching model for Early Childhood Education (PAUD), that can facilitate the learning process in developing children's characteristics from an early age. The teaching materials developed are prepared using a Project Based Learning (PBL) approach. This research includes development research or the Dick and Carey Research and Development (RnD) model. The development stages focus on children's play activities to determine instructional goals, analyze learning materials, analyze children's abilities in the context of playing while learning, assess learning targets, develop instruments, develop project learning-based learning strategies, and apply them to learning. The development of science and technology is also a challenge in line with the continuity of education which demands rapid change and adaptation to circumstances. A learning process that produces innovation in quality and competitive graduates with maximum academic and professional abilities in their fields and with personalities in line with national education goals. The research results show that teaching materials using the Project-based Learning approach can make it easier for educators to achieve goals in forming children's character from an early age through children's play activities according to their needs. On the other hand, children are required to participate actively, generate motivation, think coherently, and be assessed as being able to develop media that suits the learning needs and aspects of the child's development.